Penguatan Pendidikan Karakter Melalui Pembiasaan Sholat Dhuha Bersama di Sekolah Dasar Berbasis Islam - Mursid Mursid; Nifa Hanum Maulani (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The purpose of this study was to determine how the development of student character in Madrasah Ibtidaiyah Al Khoiriyyah 2 Semarang and how character building through dhuha prayer routine together. The type and approach of research using descriptive qualitative. Data sources were obtained through observation, interviews, and documentation. The results showed that the strengthening of student character developed from the habituation of dhuha prayer together is Religious, nasinal, Integrity, independent, and mutual cooperation.